2018
DOI: 10.5194/tc-12-491-2018
|View full text |Cite
|
Sign up to set email alerts
|

Crustal heat production and estimate of terrestrial heat flow in central East Antarctica, with implications for thermal input to the East Antarctic ice sheet

Abstract: Abstract. Terrestrial heat flow is a critical first-order factor governing the thermal condition and,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…These suggestions are consistent with more detailed regional studies, where those exist (e.g., Aitken et al, 2014;Jacobs et al, 2015;Ruppel et al, 2018). A complex interior also agrees with recent geological studies that find large age variations in marine cores (Cook et al, 2017), glacial deposits in the Transantarctic Mountains (Goodge, 2018), and what might be expected from other Gondwana continents (e.g., Begg et al, 2009;Korsch & Doublier, 2016;Kennett et al, 2018).…”
Section: New Insights Into the Lithosphere Of Antarcticasupporting
confidence: 89%
“…These suggestions are consistent with more detailed regional studies, where those exist (e.g., Aitken et al, 2014;Jacobs et al, 2015;Ruppel et al, 2018). A complex interior also agrees with recent geological studies that find large age variations in marine cores (Cook et al, 2017), glacial deposits in the Transantarctic Mountains (Goodge, 2018), and what might be expected from other Gondwana continents (e.g., Begg et al, 2009;Korsch & Doublier, 2016;Kennett et al, 2018).…”
Section: New Insights Into the Lithosphere Of Antarcticasupporting
confidence: 89%
“…The averaged shear wave velocity within the NELVZ (from ~10‐ to 25‐km depth) is consistent with shear wave velocities for granite‐gneiss to granite‐granodiorite rock types in this depth range (Christensen, ; Table ). This hypothesis provides a common source for the gravity low observed in both NE Greenland and NN and could explain regional measurements of elevated heat flow if we consider the relative thickness of this granitic layer (Pascal et al, ) and the presence of high heat‐producing granitoid rocks in NE Greenland as found in other Proterozoic terranes (Carson et al, ; Goodge, ; McLaren et al, ).…”
Section: Resultsmentioning
confidence: 92%
“…It is also difficult to determine where the thermal regime is conductive versus advective, which may be of critical importance to local conditions at the base of the ice sheet. The most significant improvement for future models of Antarctic heat flow derived from geophysical data is a more representative model of the three‐dimensional crustal architecture and resultant variations of heat production within the crust (Goodge, ).…”
Section: Discussionmentioning
confidence: 99%
“…The conventional measurement of heat flow requires access to drill holes that have recovered core samples of bedrock and direct measurement of the thermal gradient downhole (Beardsmore & Cull, ). While a small number of drill holes exist in Antarctica, they are extremely sparse in their distribution (Martos et al, ) and all measure thermal parameters only within ice or subglacial sediment; none yet have intersected the bedrock beneath (Goodge, ). Some measurements exist from offshore localities that sample sediment derived from the continental margin (Decker & Bucher, ; Dziadek et al, ; Morin et al, ).…”
Section: Geological Backgroundmentioning
confidence: 99%